Integrating CartAgO Artifacts for the Simulation of the Social Production and Management of Urban Ecosystems: the case of San Jerónimo Vegetable Garden of Seville, Spain - Santos, Flávia; Rodrigues, Henrique; Rodrigues, Thiago; Adamatti, Diana F.; Dimuro, Graçaliz P.; Dimuro, Glenda; Jerez, Esteban de Manuel (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
The paper presents some new results obtained with the modeling of a multi-agent system for the simulation of the social production and management processes of an urban ecosystem, namely, the urban vegetable garden San Jerónimo (HSJ) of Seville, Spain. The modeling was obtained by the application of several tools related to the JaCaMo platform, as the MOISE+ model for the organization modeling, the CArtAgO and MSPP frameworks for the construction of normative and communication artifacts. The aim is to provide tools for the modeling of the interactions between organizational roles when performing periodic actions in the HSJ’s social system routines. Furthermore, we show an initial proposal for integration between JaCaMo tools in the context of HSJ.